General- and Language-Specific Factors Influence Reference Tracking in Speech and Gesture in Discourse. Issue 7 (3rd October 2019) - Azar, Zeynep; Backus, Ad; Özyürek, Aslı
ABSTRACT: Referent accessibility influences expressions in speech and gestures in similar ways. Speakers mostly use richer forms as noun phrases (NPs) in speech and gesture more when referents have low accessibility, whereas they use reduced forms such as pronouns more often and gesture less when referents have high accessibility. We investigated the relationships between speech and gesture during reference tracking in a pro-drop language—Turkish. Overt pronouns were not strongly associated with accessibility but with pragmatic context (i.e., marking similarity, contrast). Nevertheless, speakers gestured more when referents were re-introduced versus maintained and when referents were expressed with NPs versus pronouns. Pragmatic context did not influence gestures. Further, pronouns in low-accessibility contexts were accompanied with gestures—possibly for reference disambiguation—more often than previously found for non-pro-drop languages in such contexts. These findings enhance our understanding of the relationships between speech and gesture at the discourse level.